Review of local binary pattern operators in image feature extraction - Hamad Khaleefah, Shihab; A. Mostafa, Salama; Mustapha, Aida; Nasrudin, Mohammad Faidzul (Institute of Advanced Engineering and Science, 2020)
With the substantial expansion of image information, image processing and computer vision have significant roles in several applications, including image classification, image segmentation, pattern recognition, and image retrieval. An important feature that has been applied in many image applications is texture. Texture is the characteristic of a set of pixels that form an image. Therefore, analyzing texture has a significant impact on segmenting an image or detecting important portions of an image. This paper provides a review on LBP and its modifications. The aim of this review is to show the current trends for using, modifying and adapting LBP in the domain of image processing.